Antidiarrheal and antispasmodic activities of Polygonum bistorta rhizomes are mediated predominantly through K+ channels activation (Bangladesh Journal of Pharmacology, 2015)
Polygonum bistorta is a popular medicinal herb used to treat diarrhea. This study provides pharmacological basis to its folk use in diarrhea using in vivo and in vitro assays. Administration of P. bistorta  rhizomes extract to mice offered protection against castor oil-induced diarrhea at 300-1,000 mg/kg and was found safe up to the dose of 5 g/kg. In isolated rabbit jejunum, the extract caused a dose-dependent relaxation of spontaneous and low K+ (25 mM)-induced contractions with weak effect against high K+ (80 mM). In tissues pretreated with glibenclamide or tetraethylammonium chloride (TEA), the relaxant effect of the extract was markedly inhibited by TEA only. While verapamil showed complete relaxation of spontaneous, low K+, low K+ with TEA and high K+-induced contractions. In guinea-pig ileum, mild atropine-sensitive effect was observed. This study indicates that P. bistorta possesses anti-diarrheal and antispasmodic activities mediated predominantly through K+-channels activation along with weak Ca++ antagonist effect.